Identification of the Heavy Metal Lead in the Industrial Area River in Buduran, Sidoarjo Regency using the Pollution Index Method - Listin Fitrianah; Ahmad Sholahudin Fawaid (G-Tech: Jurnal Teknologi Terapan, 2024)
A river is an open channel that has the function of holding and flowing water from upstream to downstream and to the estuary. The Banjarkemantren River in Buduran District is located close to industrial areas. Pollution index and water quality status refers to the Decree of the Minister of Environment No. 115 of 2003. The highest pH at sampling points AI 3 and AI 4 was 7.9. The Pb content has the same results, namely 0.038 mg/L. This value does not exceed the quality standard limit based on Government Regulation No. 82 of 2001 concerning Water Quality Standards. Determined water quality status. using the Pollution Index method. The quality status of each sample is in "Good" condition (1.0 <Plj ≤ 5.0). The water quality status of the Banjarkemantren river is in the good category.